Efisiensi Penggunaan Rontgen Periapikal dalam Mendeteksi Gigi Supernumerary Paramolar: Literature Review (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Introduction: Incidental findings often occur on periapical radiographs may occur due to the increasing use of periapical radiographs for supporting examinations and the increasing resolution of radiographs. Purpose: To explain about efficiency of periapical radiographs for detecting supernumerary paramolar teeth. Research Methods and Results: This Literature Review is designed to provide an overview of sources that have been searched when researching the topic related to the efficiency of periapical radiographs for detecting supernumerary paramolar teeth. Article searches were conducted on Google Scholar, PubMed and Science Direct using predetermined keywords, namely periapical radiograph, parapremolar, and supernumerary teeth. This literature review uses literature published in 2015–2025 which can be accessed in full text in pdf format. Discussion: Clinical assessment and radiological examination are needed for the diagnosis of supernumerary paramolar teeth. The location of supernumerary teeth from radiographs is an important diagnostic complement for clinical assessment, diagnosis, and treatment planning. Conclusion: Dentists often prefer periapical radiography over panoramic radiography to evaluate oral health, especially in children, due to the low dental X-ray exposure. In many cases, patients only require periapical radiography focused on the teeth. This highlights the strong need for intelligent diagnostic techniques to improve the accuracy and efficiency of periapical radiographic analysis.